Factors Influencing Investment in Mutual Fund Schemes of Nepal - Shrestha, Dipesh Pote; Shrestha, Yogesh Man (Journal of Business and Social Sciences Research, 2020)
The history of mutual funds in Nepal began with the introduction of “NCM Mutual Fund 2050” in 1993. The Mutual Fund Regulation, 2010 has played an important role in development of Mutual funds as momentous progress can be observed after its implementation. The mutual fund sector has raised Rs. 17.49 billion through public offering and this figure is projected to reach Rs. 19.79 billion by the end of FY 2019/20. Considering the momentous growth in the mutual fund industry this study attempts to analyse the investment pattern of Nepalese mutual fund Investors based on various parameters. This study also attempts to identify the critical factors influencing investment in mutual fund schemes of Nepal. The results indicate that the investors are moderately averse to mutual fund schemes. The results further show that the investors chose mutual fund schemes, being relied on key performance indicators of Mutual funds and their perception towards several aspects of mutual fund schemes. Moreover, fund managers’ qualities and corporate governance factors are considered important though the results are not statistically significant.